Costs of adverse events among patients with HIV infection treated with nonnucleoside reverse transcriptase inhibitors1. Issue 8 (18th March 2014) - Simpson, KN; Chen, S‐Y; Wu, AW; Boulanger, L; Chambers, R; Nedrow, K; Tawadrous, M; Pashos, CL; Haider, S
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to assess the incidence and costs of adverse events (AEs) among patients with HIV infection treated with nonnucleoside reverse transcriptase inhibitors (NNRTIs) from the health care system perspective. Methods US medical and pharmacy claims during 2004−2009 were examined to select adult new NNRTI users with HIV infection. The incidence of selected AEs and time to occurrence were assessed during the first year. Episodes of care for each AE were identified using claims associated with AE management. For each AE, a propensity score model was used to match patients with an AE to those without (1:4) based on the propensity of having an AE. Mean total health care costs, AE‐associated costs and incremental costs per episode, and annual total health care costs per patient were calculated. Results Of the 2548 NNRTI‐treated patients, 29.3% experienced AEs. The incidence ranged from 0.4 episodes/1000 person‐years for suicide/self‐injury to 14.9 episodes/1000 person‐years for dizziness, 49.8 episodes/1000 person‐years for depression and 150.3 episodes/1000 person‐years for lipid disorder. The mean AE‐associated cost (duration) per episode ranged from $586 (88 days) for lipid disorder to $975 (33 days) for rash, $2760 (73 days) for sleep‐related symptoms and $4434 (41 days) for nausea/vomiting. The mean incremental cost per episode ranged from $1580 for rash to $2032 for lipid disorder, $8307 for sleep‐related symptoms and $12 833 for nausea/vomiting. During the 12 months following NNRTI initiation, the mean annual total health care cost was $27 299 (efavirenz: $26 185; other NNRTIs: $34 993) and AE‐associated costs were $608 (efavirenz: $554; other NNRTIs: $979) among all NNRTI users. Conclusions With treatment increasing patient survival, comparisons of therapeutic regimens should consider treatment‐associated AEs. Findings from this study could be informative for clinicians and payers in managing HIV infection with NNRTIs.